ANALISIS DAMPAK IMPLEMENTASI STRATEGI CROSS SELLING PADA PENAMBAHAN DANA PIHAK KETIGA SERTA PENAMBAHAN JUMLAH NASABAH FUNDING DI PERUMDA BPR BANK DAERAH KOTA MADIUN - Handaru Handaru Agnyana; Choirum Rindah Istiqaroh; Novy Rachma Herawati; Paris Cahyono (Universitas Merdeka Madiun, 2024)
The main objective of this research is to investigate how the cross-selling strategy is applied and how it affects the collection of third party funds. Second, examine the obstacles to cross selling strategies in raising third party funds. Third, look into how the cross-selling approach is being used and how that is affecting the amount of money raised for third party funds. This study uses a field research methodology and is qualitative-descriptive in nature. Madiun City Regional Bank, People's Credit Bank (BPR), and Regional Public Company (Perumda) served as the research subjects. This study's objective is to develop a cross-selling strategy that will boost third-party funding. Documentation, interviews, and observation are methods used to collect data. The three stages of the data analysis procedure were data reduction, data display, and conclusion drawing. To determine the veracity of the data, take into account using source triangulation. First, the research's findings indicate that the Tabunganku Product becomes the primary account when cross-selling is implemented. Furthermore, you can get other services, namely having more than one savings product account, lower credit interest, receiving deposit interest and disbursing credit through your Tabunganku account. Second, the obstacles are competition with conventional banks, savings cannot be disbursed at any time, and lack of communication with customers. Third, the impact that arises is customer loyalty, increasing income, reducing time and costs, and maintaining public trust in using third party fund products.